Experimental Study on Performance Characteristics of a Pem Fuelcell - Ale, B. B.; Shrestha, S.O. Bade (Journal of the Institute of Engineering, 2009)
The performance of a PEM fuel cell was investigated for different operating conditions. The fuel cell was tested for different dew point temperature of humidifier, the stack coolant temperature, and stoichiometric of fuel and air supply conditions. The higher stack coolant temperature, humidity, as well as stoichiometric of reactants produced enhanced performance of the fuel cell as expected. The effect on the cell voltage and efficiency were more pronounced as the current density was increased to medium and high levels. The deteriorating and degradation effect of the performance of the fuel cell was also observed during the test span. Keywords: Pem Fuelcell, Nepal Journal of the Institute of Engineering, Vol. 7, No. 1, 2009 July pp. 31-39 doi: 10.3126/jie.v7i1.2060